2021
DOI: 10.3389/fendo.2021.741698
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography-Based Radiomics Model to Predict Central Cervical Lymph Node Metastases in Papillary Thyroid Carcinoma: A Multicenter Study

Abstract: ObjectivesThis study aimed to develop a computed tomography (CT)-based radiomics model to predict central lymph node metastases (CLNM) preoperatively in patients with papillary thyroid carcinoma (PTC).MethodsIn this retrospective study, 678 patients with PTC were enrolled from Yantai Yuhuangding Hot3spital (n=605) and the Affiliated Hospital of Binzhou Medical University (n=73) within August 2010 to December 2020. The patients were randomly divided into a training set (n=423), an internal test set (n=182), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…metastasis in PTC (29,36,37). These results suggested that radiomics models help to improve the diagnostic accuracy of cervical LN metastasis.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…metastasis in PTC (29,36,37). These results suggested that radiomics models help to improve the diagnostic accuracy of cervical LN metastasis.…”
Section: Discussionmentioning
confidence: 80%
“…Radiomics extracts hundreds of quantitative features from images, and self-training and learning are conducted based on the pathological results to assist in clinical diagnosis ( 24 28 , 35 ). Available studies have been conducted to develop radiomics models based on CT or US images to predict cervical LN metastasis or lateral cervical LN metastasis in PTC ( 29 , 36 , 37 ). These results suggested that radiomics models help to improve the diagnostic accuracy of cervical LN metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The SVM was used to obtain the best predictive radiomics model. An SVM is an effective, powerful, and robust machine learning classifier used primarily in radiology ( 25 , 26 ). In this study, SVM had faster training and classification speed than RF, KNN, LR, GBDT, and XGBOOST, because it was most suitable for high-dimensional features ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that radiomics can be used to describe tumor phenotypes, distinguish benign and malignant tumors, and predict lymph node metastasis and outcomes (7). Radiomics models have been shown to predict lymph node metastasis in PTC (8,9), and CT-based radiomics models are also valuable in the differentiation of benign and malignant lymph nodes in the head and neck (10). Few studies have examined the differentiation of metastatic and nonmetastatic lymph nodes among patients with PTC and the classification of reactive hyperplastic lymph nodes among patients with benign thyroid lesions.…”
Section: Introductionmentioning
confidence: 99%